2017
DOI: 10.3390/molecules23010070
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazone Derivatives Enhance Antileishmanial Activity of Thiochroman-4-ones

Abstract: Cutaneous leishmaniasis (CL) is a neglected tropical disease, which causes severe skin lesions. Due to the lack of effective vaccines, and toxicity or reduced effectiveness of available drugs in addition to complex and prolonged treatments, there is an urgent need to develop alternatives for the treatment for CL with different mechanisms of action. In our effort to search for new promising hits against Leishmania parasites we prepared 18 acyl hydrazone derivatives of thiochroman-4-ones. Compounds were evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Finally, it has been noted that the thiazolidinone core has become a key candidate for the development of drugs with anti- Toxoplasma activity. It was also observed that moiety hydrazone was preserved in all studies, which suggests that this moiety is also part of a possible promising scaffold with antiparasitic activity, and recent studies suggest that the presence of moiety hydrazone on the drug would be potentiating its biological activity (Leite et al, 2017 ; Vargas et al, 2018 ). It is worth to mention that there are also numerous studies in which the use thiazolidinone-like structural core against T. gondii are reported, for example the thiazole core, for which a broad spectrum of biological activity, including anti- Toxoplasma , has also been documented (Chimenti et al, 2009 ; Hencken et al, 2010 ; McFarland et al, 2016 ).…”
Section: Thiazolidinones Core On Toxoplasma Gondii mentioning
confidence: 80%
“…Finally, it has been noted that the thiazolidinone core has become a key candidate for the development of drugs with anti- Toxoplasma activity. It was also observed that moiety hydrazone was preserved in all studies, which suggests that this moiety is also part of a possible promising scaffold with antiparasitic activity, and recent studies suggest that the presence of moiety hydrazone on the drug would be potentiating its biological activity (Leite et al, 2017 ; Vargas et al, 2018 ). It is worth to mention that there are also numerous studies in which the use thiazolidinone-like structural core against T. gondii are reported, for example the thiazole core, for which a broad spectrum of biological activity, including anti- Toxoplasma , has also been documented (Chimenti et al, 2009 ; Hencken et al, 2010 ; McFarland et al, 2016 ).…”
Section: Thiazolidinones Core On Toxoplasma Gondii mentioning
confidence: 80%
“…Compound 6, meanwhile, had the lowest cytotoxicity, possibly associated with the presence of the arylhydrazone group. Several studies have described the use of hydrazone derivatives with leishmanicidal activity, reporting their good selectivity rates and low cytotoxicity [31,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, this task is a priority for the pharmaceutical industry, so the affected countries must seek their own alternatives. Recently we reported the in vivo leishmanicidal activities of compounds bearing a benzothiopyran scaffold and also the acyl hydrazones derived from chroman and thiochromans [8,23]. To optimize their effects, in this work we prepared thirty-two compounds, including thiochromenes, thichroman-4-ones and acyl hydrazones substituted in C-2 or C-3 with carbonyl/nitrile or carboxyl groups.…”
Section: Discussionmentioning
confidence: 99%